Denitrification at two nitrogen-polluted, ombrotrophic Sphagnum bogs in Central Europe: Insights from porewater N2O-isotope profiles. (February 2015) - Novak, Martin; Gebauer, Gerhard; Thoma, Michael; Curik, Jan; Stepanova, Marketa; Jackova, Ivana; Buzek, Frantisek; Barta, Jiri; Santruckova, Hana; Fottova, Daniela; Kubena, Ales A.
Abstract: Measurements of nitrogen isotope ratios (δ 15 N) along vertical porewater profiles are instrumental in localizing sources and sinks of nitrous oxide (N2 O) in wetland ecosystems. We present the first N2 O concentration and isotope data for porewaters of ombrotrophic, mountain-top bogs. Our two study sites, situated in the Czech Republic at elevations higher than 1000 m, have been affected by atmospheric N pollution for more than 100 years. In recent decades, the northeastern site KB received over 30 kg N ha −1 yr −1 via atmospheric deposition, the southwestern site BS was 3 times less polluted. Both peat bogs were surrounded by defoliated, dead spruce stands. We hypothesized that elevated nitrate (NO3 − ) inputs in rain-fed bogs may cause sizeable N2 O emissions. Porewater N2 O concentrations in the studied ombrotrophic bogs were 400–800 times higher, compared to fens in nearby Bavaria (Germany). The highest N2 O concentrations and the lowest δ 15 N–N2 O values were found at the bottom of the sampled porewater profiles, 40–60 cm below surface. Low δ 15 N–N2 O values resulted from a N isotope fractionation associated with denitrification. The site with the lower historical N pollution, BS, exhibited up to 7 times higher porewater N2 O concentrations than KB, possibly due to a higher denitrification potential determined as abundance of nir K and nir S genes. Upcore, N2 O abundance decreased and δ 15 N–N2 O increased, indicating N2 O reduction. Processes of N2 O formation and consumption at different depths were integrated by measuring N2 O fluxes across the peat – atmosphere interface. These fluxes were minute (<0.02 μmol N2 O m −2 h −1 ). We even observed scavenging of air-borne N2 O by the bog substrate. Nitrogen pollution of ombrotrophic bogs led to vigorous N cycling, manifested by extremely high peat porewater N2 O concentrations. However, effective in-situ consumption of the produced N2 O greatly reduced its warming potential. Highlights: We report the first porewater N2 O isotope data for N-polluted rain-fed bogs. Downcore, N2 O concentrations were 800 times higher than at minerotrophic fens. Despite that, efficient N2 O reduction in situ prevented high N2 O emissions from peat. Residual N2 O–N in porewater was isotopically heavier than deposited N and substrate N. Bogs receiving 50 kg N/ha/yr via rainfall may still act as a sink for air-borne N2 O.